Microbiota and the gut-liver axis: Bacterial translocation, inflammation and infection in cirrhosis - Giannelli, Valerio (World J Gastroenterol, 2014)
Liver disease is associated with qualitative and quantitative changes in the intestinal microbiota. In cirrhotic patients the alteration in gut microbiota is characterized by an overgrowth of potentially pathogenic bacteria (i.e., gram negative species) and a decrease in autochthonous familiae. Here we summarize the available literature on the risk of gut dysbiosis in liver cirrhosis and its clinical consequences. We therefore described the features of the complex interaction between gut microbiota and cirrhotic host, the so called “gut-liver axis”, with a particular attention to the acquired risk of bacterial translocation, systemic inflammation and the relationship with systemic infections in the cirrhotic patient. Such knowledge might help to develop novel and innovative strategies for the prevention and therapy of gut dysbiosis and its complication in liver cirrhosis.